PCL/β-AgVO3 nanocomposites obtained by solvent casting as potential antimicrobial biomaterials - de Menezes, Beatriz Rossi Canuto; Montanheiro, Thaís Larissa do Amaral; Sampaio, Aline da Graça [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Thim, Gilmar Patrocínio; Montagna, Larissa Stieven (Wiley, 2021)
The adhesion of microorganisms on biomaterials can impair its effective application. The addition of antimicrobial agents is a promising alternative to overcome this limitation. In this work, films of polycaprolactone (PCL) and nanostructured β-AgVO3 (SV) were produced by solvent casting with 0.1, 0.5, and 1.0 wt% of SV. The effect of SV on the structure of PCL was investigate using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Raman spectroscopy, differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). The antimicrobial activity of the films against Staphylococcus aureus and Escherichia coli was evaluated by the agar diffusion method and by direct contact test. FTIR confirmed the presence of SV into the PCL films, with chemical interaction between them. SEM showed that SV nanorods were well dispersed and with good interfacial adhesion with PCL. XRD diffraction and Raman spectroscopy showed that the presence of SV increased the number of nucleation sites, reducing the size of crystallites and increasing the amorphous domains in the PCL matrix, consequently reducing crystallinity. This behavior was confirmed by DSC, which showed a reduction in the crystallinity with increasing SV content. Films with 1 wt% of SV showed antimicrobial activity against Staphylococcus aureus in direct contact test.
Keywords: biocompatibility; biomedical applications; films; nanoparticles; nanowires and nanocrystals